Psychological assistance to patients with thyroid cancer - G. A. Tkachenko; T. I. Grushina; Yu. V. Alymov; S. O. Podvyaznikov (Опухоли головы и шеи, 2023)
Introduction. Thyroid cancer has a favorable prognosis but in long term patients are observed to be in psychological distress manifesting through elevated anxiety and depression which disrupt social adaptation. Studies have shown that 2–4 years after diagnosis and treatment of this malignant tumor, the majority of patients report dissatisfaction with family relationships and difficulties in performing everyday activities. These data demonstrate the necessity of rehabilitation aimed at patient adaptation to everyday life after therapy completion. Psychological help is an important aspect of rehabilitation.Aim. To evaluate the effectiveness of psychological help in patients with thyroid cancer.Materials and methods. The study included 42 women with thyroid cancer, stages I–III, Т1–3N0–1М0. Mean patient age was 44.5 ± 1.1 years. The patients were randomly divided into 2 groups matched by age, disease stage and type of surgical intervention: treatment and control groups. The treatment group (n = 24) included patients who underwent psychological training in the postoperative period, the control group (n = 18) included patients who did not receive psychological help. Mental state was evaluated using the Hospital Anxiety and Depression Scale (HADS). The patients’ mental state was evaluated dynamically: 1st testing was performed after surgery, 2nd testing 12 months after surgery. Psychological training was performed in the postoperative period and included 5 individual classes teaching self-regulation skills.Results. After the surgery, HADS scale showed insignificant increase in anxiety in both groups. Analysis of repeat testing showed decreased anxiety levels in patients in the treatment group from 7.7 ± 0.2 to 6.3 ± 0.2, i. e. to normal level. In the control group, anxiety significantly increased from 7.8 ± 0.2 to 9.2 ± 0.2 (Student’s t-test = 5.17; p = 0.000168). Additionally, 12 months after surgical treatment statistically significant differences in anxiety levels between groups were observed: 6.3 ± 0.2 and 9.0 ± 0.2, respectively (Student’s t-test = 9.55; р <0.05). Primary examination showed subthreshold depression in patients of both groups: 7.9 ± 0.1 and 8.1 ± 0.2, respectively. No statistically significant differences between the groups were observed (Student’s t-test = 0.89; р >0.05). Repeat examination showed decreased depression level (in treatment group from 7.9 ± 0.1 to 7.4 ± 0.2, in the control group from 8.1 ± 0.2 to 7.7 ± 0.1), however it remained in the range of mean values. No statistically significant differences between the groups were observed (Student’s t-test = 1.34; р >0.05).Conclusion. Psychological training using self-regulation techniques performed in the early postoperative period normalizes anxiety level and prevents its elevation in long term in patients with thyroid cancer.